The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00438-014-0906-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel in vitro inhibitory functions of potato tuber proteinaceous inhibitors

Abstract: Plant protease inhibitors are a structurally highly diverse and ubiquitous class of small proteins, which play various roles in plant development and defense against pests and pathogens. Particular isoforms inhibit in vitro proteases and other enzymes that are not their natural substrates, for example proteases that have roles in human diseases. Mature potato tubers are a rich source of several protease inhibitor families. Different cultivars have different inhibitor profiles. With the objective to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 54 publications
(80 reference statements)
1
17
0
2
Order By: Relevance
“…Recently, a cDNA library was obtained from several potato cultivars and some proteins were heterologously expressed and tested against different classes of proteases. This work showed that inhibition of aspartic proteases is also possible in potato protease inhibitors belonging to group B (Fischer et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Recently, a cDNA library was obtained from several potato cultivars and some proteins were heterologously expressed and tested against different classes of proteases. This work showed that inhibition of aspartic proteases is also possible in potato protease inhibitors belonging to group B (Fischer et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…The 2F o -F c electron density maps of the E3Ad and E3Ad_N19D inhibitor structures clearly showed the presence of three disulfide bridges between positions Cys48-Cys93, Cys142-Cys158 and Cys148-Cys152. These disulfide bridges are present in all Kunitz-type STI family inhibitors able to inhibit aspartic proteases characterized to date, except those classified as part of the group B (Cater et al, 2002;Fischer et al, 2015;Keilová and Tomášek, 1976a;Mares et al, 1989).…”
Section: Overall Structure Of the Bi-functional Inhibitors E3ad And Mmentioning
confidence: 98%
See 2 more Smart Citations
“…2011. El continuo avance en el conocimiento de su acción ha dado lugar a numerosos recientes reportes que expresan su potencial reemplazo de terapias con drogas sintéticas en la farmacología (Atanasov A G. 2015, Fischer 2015. Esperamos que la discusión de este trabajo resulte provechosa para el avance del estudio de esta clase de moléculas.…”
Section: Discussionunclassified